Harnessing Particle Size‐Control and DNA‐Oligo Functionalization in ZIF‐76 for Biological Applications. Issue 5 (1st December 2022) - Deneff, Jacob I.; Butler, Kimberly S.; Reyes, Raphael A.; Sava Gallis, Dorina F.
Abstract: Advanced therapeutics require novel nanocarriers to ensure their functionality is preserved during transit. Zeolitic imidazolate frameworks (ZIFs) have emerged as promising materials in this field owing to their combined biocompatibility, high porosity, and tunable chemistry. While a diverse family of ZIFs has been reported, few have been explored beyond the prototypical ZIF‐8. Herein, the size‐controlled synthesis of three distinct ZIF‐76 analogs is demonstrated, overcoming the unique synthetic challenges intrinsic to the lta topology and complex crystallization kinetics associated with the mixed linker approach. This assesses the materials' platform effectiveness for intracellular delivery first by exploring the structural and colloidal stability in biologically relevant media. To circumvent particle aggregation, fluorescently labeled DNA oligonucleotides are post‐synthetically attached to the ZIF surface. This modification significantly improves the colloidal stability in media and facilitates particle internalization tracking. Finally, the particle‐cell interactions are assessed, revealing rapid cell membrane association with macrophages, but not lung epithelial cells, and ZIF accumulation within macrophages which increased over time. Importantly, this study outlines a generalized approach toward expanding the available library of ZIFs for biological applications, enabling the potential for targeted therapeutic delivery for intracellular infections treatment. Abstract : Size‐controlled synthesis of three zeolitic imidazolate framework (ZIF)‐76 analogs is achieved by tuning precursor concentration. Colloidal stability is enhanced via post‐synthetic addition of deoxyribonucleic acid (DNA) oligonucleotides. Short‐term incubation of ZIF‐76@DNA showed significant association with macrophages, but not epithelial cells. Further, increased incubation times resulted in time dependent uptake in macrophages, showing the potential of ZIF‐76 analogs for biological applications.